A life cycle assessment of annual, N fertilised perennial and non-N fertilised perennial pastures, South-Western Australia. (2015) - Biswas, Wahidul K.
This research aims to assess the emissions of greenhouse gases (GHGs) from one kilogram of live weight cattle production from annual pastures, nitrogen (N) fertilised perennial pastures and non-N fertilised perennial pastures in Western Australia for different farming practices. Using streamlined life cycle assessment (SLCA) methodology, it was estimated that approximately 14.30 kg, 12.09 kg and 11.0 kg of CO2 -e of GHG emissions will be emitted from the production of one kilogram of live weight cattle from annual, non-N fertilised and N fertilised perennial pastures respectively. Enteric emissions account for a significant portion of GHG emissions (85% from annual pasture and around 95% from perennial pastures). Live weight yields from annual pasture emit more GHG emissions than do N fertilised and non-N fertilised perennial pastures. Although the inclusion of liming produces additional GHG emissions, the increase in productivity associated with these activities can actually offset GHG emissions when considered on a per kilogram basis.